1993
DOI: 10.1109/58.238102
|View full text |Cite
|
Sign up to set email alerts
|

Design of SAW FIR filters for quadrature binary modulation systems

Abstract: Approaches for designing surface acoustic wave (SAW) filters used in pulsed quadrature binary modulation (QBM) systems are presented. Several previously defined pulse shapes were implemented by a SAW filter and showed good QBM system performance with respect to modulation envelope nonuniformity (AM) and intersymbol interference (ISI). A new approach to QBM pulse shape definition using both frequency- and time-domain design criteria is described. This approach allows families of new pulse shapes having various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As shown in the previous literature, Lu et al extracted a novel electrode-area-weighted (EAW) method of implementing wavelet transform processor (WTP) with SAW device based on X-112 • Y LiTaO 3 [6]. A. J. Vigil et al presented approaches for SAW filter design used in pulsed Quadrature Binary Modulation (QBM) systems with split interdigital transducer (IDT) [7]. Ye et al reported YZ-cut LiNbO 3 is suitable for the fabrication of SAW temperature sensors for its higher sensitivity and larger Q factor [8].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the previous literature, Lu et al extracted a novel electrode-area-weighted (EAW) method of implementing wavelet transform processor (WTP) with SAW device based on X-112 • Y LiTaO 3 [6]. A. J. Vigil et al presented approaches for SAW filter design used in pulsed Quadrature Binary Modulation (QBM) systems with split interdigital transducer (IDT) [7]. Ye et al reported YZ-cut LiNbO 3 is suitable for the fabrication of SAW temperature sensors for its higher sensitivity and larger Q factor [8].…”
Section: Introductionmentioning
confidence: 99%